Prenatal ultrasonographic manifestations of partial trisomy 12q(12q24.2→qter) and partial monosomy 2q (2q37.3→qter) - Joksić, Ivana; Liehr, Thomas; Toljić, Mina; Karadžov Orlić, Nataša; Milovanović, Zagorka; Miković, Željko; Egić, Amira (Vojnosanitetski pregled, 2021)
Introduction. Partial trisomy of chromosome 12 long arm is rare condition with significant clinical impact and is usually diagnosed postnatally. Case report. We present prenatal sonographic findings and molecular cytogenetic characterization of partial trisomy 12q and partial monosomy 2q in two consecutive pregnancies of a healthy non-consanguineous couple. A 35-year-old pregnant woman G3P1A1 was referred to genetic counseling due to sonographic anomalies detected in the fetus. First trimester ultrasound examination revealed hyperechogenic focus in the left cardiac ventricle, single umbilical artery, hyperechogenic bowel and unilateral clubfoot with knee joint ankylosis. Previous pregnancy of the couple was terminated at 26th gestation weeks due to multiple fetal anomalies: bilateral ventriculomegaly, corpus callosum hypoplasia, single umbilical artery and clubfoot. In G3P1A1, amniocentesis was performed and cytogenetic analyses revealed a derivative chromosome 2. Subsequent cytogenetic analyses of parental lymphocytes showed that paternal karyotype was normal, while maternal karyotype showed a der(2). Metaphase fluorescence in situ hybridization (FISH) studies demonstrated partial trisomy 12q24.2→12qter and partial monosomy 2q37.3→2qter in the fetus, resulting from an unbalanced segregation of a maternal balanced translocation t(2;12)(q37.3;q24.2). To date, this is the first such prenatally detected case. Literature search revealed three more cases of prenatally detected partial trisomy 12q and anomalies described were consistent with ones detected in present case. Our findings contribute to further clinical delineation of partial trisomy 12q. Conclusion. Prenatal detection of single umbilical artery, clubfoot, arthogryposis and ventriculomegaly should alert suspicion to chromosome 12q aberrations.